Determination of amino acid digestibility and calculated energy values in high-protein sorghum dried distillers grains with solubles in growing pigs - Frobose, H.L.; Jacela, J.Y.; DeRouchey, Joel M.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
An experiment was conducted to determine the digestibility of amino acids (AA) and energy in high-protein sorghum dried distillers grain with solubles (DDGS). Six growing barrows (initially 50 lb) surgically fitted with T-cannulas were randomly assigned to 1 of 2 dietary treatments in a 2-period crossover design. The treatments were a diet with the high-protein sorghum DDGS (50% of the diet) as the only protein source and an N-free diet for determining basal endogenous AA loss. Both diets contained 0.25% chromic oxide as an indigestible marker. Fecal and ileal digesta samples were collected during each period for energy and AA analysis. On the basis of these analyses, apparent (AID) and standardized (SID) ileal digestibility and energy values were calculated. The analyzed CP of the product was 44.5% with a lysine:CP ratio of 3.6%. Crude fat, ADF, and NDF were 2.9, 16.1, and 18.8%, respectively. The AID for lysine, methionine, threonine, and tryptophan were 51.9, 73.0, 60.6, and 71.7%, respectively. The SID values were 53.7, 73.8, 63.0, and 73.8% for lysine, methionine, threonine, and tryptophan, respectively. The analyzed GE of the product was 2,317 kcal/lb of DM. The calculated DE, ME, and NE values were 1,759; 1,610; and 1,023 kcal/lb of DM, respectively. In conclusion, the high-protein sorghum DDGS is higher in CP, AA, Ca, and P but lower in AA digestibility and energy compared with reported values for traditional DDGS.
Keywords: Amino acid; Digestibility; Dried distillers grains with solubles; Sorghum; Swine